PEMODELAN EARLY WARNING SYSTEM UNTUK PREVENTIVEMAINTENANCE PADA PT.CIGADING HABEAM CENTER - Leonardus Arthur Suteja (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
In the industrial era PT Cigading Habeam Center is engaged in fabrication to increaseproduction capacity by powered machinery production quality and have modern technology, inan effort to increase the stability of production, the company should maintain optimumproduction machinery. Then maintenance effort by the Division is required to performmaintenance of these machines. In an effort to implement preventive maintenance withApplication Early Warning System for Computerized-based Preventive Maintenance is veryimportant.In reaching this preventive maintenance treatment, using data obtained decay interval field tothe stages of the calculation index of fit for each component and calculate the parameters ofMean Time To Failure (MTTF) to obtain the optimal change at any time spareparts. Theturnover time of the reference optimal schedule change spareparts, In supporting turn right ontime, so it takes a reminder system, an early warning system or Early Warning System for theturn spareparts. Draft Model Early Warning System produces signals to indicate the spareparts must be replaced.